2004
DOI: 10.1097/01.hjr.0000124327.85096.a5
|View full text |Cite
|
Sign up to set email alerts
|

Functional and morphological skeletal muscle abnormalities correlate with reduced electromyographic activity in chronic heart failure

Abstract: Our findings demonstrate an impaired electromyographic activity and muscular function in patients with CHF suggesting a new pathomechanism contributing to functional abnormalities of the skeletal muscle in advanced stages of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 38 publications
0
20
0
2
Order By: Relevance
“…Although we acknowledge that these relationships are not necessarily causal, previous studies (28,29) have demonstrated that exercise training induces a concomitant increase in muscle oxidative capacity and skeletal muscle endurance in patients with CHF, thus supporting the existence of a link between skeletal muscle endurance and oxidative capacity. Of note, we cannot exclude the possibility that the increased susceptibility to fatigue in CHF may, in part, be related to abnormal motor unit recruitment (30). However, the existing relationships between T F and various muscle enzyme activities also support the contention that the metabolic capacity of the vastus lateralis muscle was equally important in explaining reduced muscle endurance.…”
Section: Discussionmentioning
confidence: 80%
“…Although we acknowledge that these relationships are not necessarily causal, previous studies (28,29) have demonstrated that exercise training induces a concomitant increase in muscle oxidative capacity and skeletal muscle endurance in patients with CHF, thus supporting the existence of a link between skeletal muscle endurance and oxidative capacity. Of note, we cannot exclude the possibility that the increased susceptibility to fatigue in CHF may, in part, be related to abnormal motor unit recruitment (30). However, the existing relationships between T F and various muscle enzyme activities also support the contention that the metabolic capacity of the vastus lateralis muscle was equally important in explaining reduced muscle endurance.…”
Section: Discussionmentioning
confidence: 80%
“…Heart disease is one of the most common chronic conditions in older adults (National Advisory Council on Aging 2006). Patients with heart failure have greater muscle fatigue than healthy older adults (Brassard et al 2006;Schulze et al 2004) (Table 3). The impaired muscle function observed in heart failure patients may be explained by their reduced muscle strength, muscle mass, muscle blood flow, and muscle oxidative capacity, and increased proportion of type II muscle fibers, lactate accumulation, acidosis, and reliance on glycolytic metabolism (Brassard et al 2006;Schulze et al 2004).…”
Section: Diseasementioning
confidence: 99%
“…24 Excitation-contraction (E-C) coupling initiates the contraction of the myocardial muscle following the release of Ca 2+ from ryanodine receptors in the sarcoplasmic reticulum in response to voltage-gated Ca 2+ channels in the transverse tubules. 25,26 In HF, myocardial E-C coupling is impaired due to a variety of mechanisms such as a sarcoplasmic Ca 2+ leak, elevated cellular Na + levels, and structural remodeling.…”
Section: Discussionmentioning
confidence: 99%